STRATEGY ANALYSIS OF BUILDING CUSTOMER LOYALTY INDIHOME PT. TELECOMMUNIKASI INDONESIA Tbk - Dhery Wiranata Surya; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2023)
Looking at the emerging internet service competitors, it is hoped that IndiHome will become one of the providers offering the best internet access and services. High consumer loyalty for a product is the most important aspect for a company in carrying out its business activities. To increase consumer loyalty, companies must pay attention to the factors that become a benchmark for consumer loyalty, including product, price, place, promotion, people, process, and physical evidence. The type of research used is quantitative, with a research method that is correlational research which is defined as a research method based on the philosophy of positivism, used to examine certain populations or samples, sampling techniques are carried out randomly, and data collection uses research instruments. The study results show that the product (product) positively and significantly affects IndiHome consumer loyalty at PT. Telkom witel Medan. Price has a positive and insignificant effect on IndiHome consumer loyalty. Promotion has a positive and significant effect on IndiHome consumer loyalty. People have a positive and insignificant effect on consumer loyalty. The process (process) positively and significantly affects consumer loyalty. Customer satisfaction has a positive and significant effect on consumer loyalty.